Tether: A Study on Bubble-Networks - Rosa, Giovanni; Pareschi, Remo (Frontiers in Blockchain, 2021)
Tether is a stablecoin, namely a cryptocurrency associated with an underlying security (in this case the US Dollar), mainly traded through Bitfinex, one of the largest Bitcoin exchanges. Tether provides one of the most popular ways to buy bitcoins and has been the centre of many controversies. In fact, it has been hypothesized that new tethers are issued without the underlying dollars being actually kept in reserve, thus infringing the requirement that for every tether there has to be one dollar to back it, and that new massive Tether emissions are the basis of strong speculative movements on the Bitcoin. In the course of this article, we conduct a Social Network Analysis (SNA) focused on the Tether transaction graph to identify the main actors that play a leading role on the network and characterize the transaction flow between them. The conclusion is that Tether flows on a network that generates and reflects the bubble effects in the price of the Bitcoin it is associated with. Beyond the specific scope of analyzing the behavior of the Tether, we see our contribution as a step towards a network-based investigation of the bubble phenomenon.